Presbyopia compensation with a light sword optical element of a variable diameter - Petelczyc, Krzysztof; Ares Garcia, Jorge; Bará, Salvador; Jaroszewicz, Zbigniew; Kołodziejczyk, Andrzej; Sypek, Maciej (Photonics Letters of Poland, 2009)
This paper presents preliminary results of numerical analysis of imaging quality of a refractive light sword optical element (LSOE) in the function of its diameter. For comparison other optical imaging elements with extended focal depth, such as the bifocal lens, and the forward axicon, were also checked. The parameters of all elements were assumed according to the human eye parameters in order to check possibilities of presbyopia compensation. Obtained results allow to state that in contrary to other analyzed elements the LSOE’s performance and the length of the focal segment do not depend on its diameter.